INTERACTION BETWEEN JUDGES AND EXPERT WITNESSES IN THE COURSE OF CIVIL PROCEEDINGS - O. Zhukova (Теория и практика судебной экспертизы, 2015)
The paper looks at some problems associated with the appointment of forensic examinations, preparation of materials in the course of forensic examination, and assessment of forensic expert reports in court.